Wheat challenge in self-reported gluten sensitivity: a comparison of scoring methods. (1st February 2017) - Skodje, Gry I.; Henriksen, Christine; Salte, Trude; Drivenes, Thea; Toleikyte, Ieva; Lovik, Astrid M.; Veierød, Marit B.; Lundin, Knut E.A.
Abstract: Background: The condition non-coeliac gluten sensitivity (NCGS) is clinically similar to coeliac disease, but lack objective diagnostic criteria. Symptom relief on gluten-free diet followed by gluten containing food challenge may confirm the condition in clinical settings. Aim: To describe the results of an open bread challenge in patients with suspected NCGS, and to compare the results with recently suggested cut-offs for symptom change. Material and methods: Fifty-six patients (12 males) self-instituted on gluten-free diet with negative coeliac disease diagnostics were examined for NCGS by an open bread challenge. Symptoms were reported by Gastrointestinal Symptom Rating Scale, IBS-version (GSRS-IBS) and visual analogue scale (VAS). Results were retrospectively compared to the Salerno and Monash cut-offs for symptom change. Results: Forty-seven patients were diagnosed with NCGS. Total GSRS-IBS score and overall symptoms by VAS increased significantly in NCGS ( p  < .001), but not in non-NCGS patients ( p  < .12 and p  = .08, respectively). Total GSRS-IBS challenge score and overall symptoms by VAS were significantly higher in NCGS than in non-NCGS patients (53 vs. 37, p  = .004 and 76 vs. 39 mm, p  = .02, respectively). Applying the Salerno and Monash cut-offs, 63 and 75% would be classified with NCGS, respectively. According to total GSRS–IBS absolute agreement was lowest between clinician's diagnosis and Salerno cut-off (63%) and highest between Salerno and Monash cut-offs (88%). Conclusion: Clinician diagnosed 85% with NCGS. The proportion of NCGS was lower according to the Salerno and Monash cut-offs. The Salerno cut-off should be the starting point for a common definition of symptom change.